A Rare Complication of Fine-Needle Aspiration of Neck Structures - Yazeed M. Qadadha; Nainika Nanda; Chad Ennis; Timothy McCulloch (Case Reports in Otolaryngology)
Fine-needle aspiration (FNA) is a generally accepted tool for safe diagnostic evaluation in the workup of lesions and masses. Aside from the commonly discussed risks of infection and minor bleeding related to skin puncture, other more serious complications have been reported sparingly. We present two cases of pneumothorax from FNA of neck structures, which have been theorized but not previously reported to our knowledge. Discussion of cases of this complication rather than solely a theoretical understanding of it will aid in diagnosis and management of this complication.